Lithogenic, oceanic and anthropogenic sources of atmospheric Sb to a maritime blanket bog, Myrarnar, Faroe Islands - Shotyk, William; Chen, Bin; Krachler, Michael (Journal of environmental monitoring, 2005)
Antimony concentrations were measured in a core collected from Myrarnar, a blanket bog on the Faroe Islands which has been accumulating peat for more than six thousand years. The vertical distribution of Sb indicates that it has been supplied to the peat exclusively from the atmosphere. Despite the proximity to the ocean, the contribution of Sb to the peat from marine aerosols amounts to less than ca. 10% of the natural inputs. Although the peat core contains four notable layers of volcanic ash originating from Iceland, these have not contributed significantly to the Sb inventory. However, the distribution of Sb closely resembles that of Pb, with most of the Sb found in peats dating from the industrial period. Peat samples dating from the Roman Period are not only contaminated with Pb, but also with Sb. Lead is known to be immobile in peat bogs, and in Europe has been derived predominantly from industrial sources for thousands of years. The correlation between Sb and Pb in the peat core from the Faroe Islands supports the hypothesis that Sb is also effectively immobile in peat, and that ombrotrophic bogs are faithful archives of atmospheric Sb deposition. The data presented here also reinforces the view that natural Sb inputs during the past two centuries are dwarfed by industrial inputs, and that human activities have affected the atmospheric Sb cycle to a comparable extent to that of Pb. The natural rate of atmospheric Sb deposition recorded by the peat core (0.33 μg m−2 year−1) is remarkably similar to the value obtained from a Swiss peat bog (Etang de la Gruère) in the samples dating from ca. 6000 to 9000 years ago (0.35 μg m−2 year−1) which suggests that the background rates obtained from the peat cores have broader validity. Consistent with previous work, the data from the Faroe Islands suggests that the natural flux of Sb to the global atmosphere may have been overestimated by a factor of ten, and that the influence of human activities has been underestimated to the same extent.